The Vps35 D620N Mutation Linked to Parkinson's Disease Disrupts the Cargo Sorting Function of Retromer. (14th November 2013) - Follett, Jordan; Norwood, Suzanne J.; Hamilton, Nicholas A.; Mohan, Megha; Kovtun, Oleksiy; Tay, Stephanie; Zhe, Yang; Wood, Stephen A.; Mellick, George D.; Silburn, Peter A.; Collins, Brett M.; Bugarcic, Andrea; et al.
<x xml:space="preserve">Abstract</x> A genetic mutation in the Vps35 subunit of retromer has recently been linked to late onset Parkinson's disease. We observed that the distribution and maturation of Vps35 D620N positive endosomes are altered. While Vps35 D620N containing retromer still binds CI‐M6PR, its trafficking is perturbed as shown by secretion of its ligand cathepsin D. As cathepsin D is involved in processing of α‐synuclein, a well‐established causative agent of Parkinson's disease, its altered trafficking may therefore represent the underlying cause of disease.<boxed-text content-type="graphic" id="tra12136-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>